Synthesis and Validation of a Weatherproof Nursery Design That Eliminates Tropical Evening-Fever Syndrome in Neonates - Hippolite O. Amadi; Lawal I. Mohammed; Mohammed B. Kawuwa; Abdulquddus Oyedokun; Hajjah Mohammed (International Journal of Pediatrics)
Neonatal thermal stabilisation can become challenging when uncontrollable factors result in excessive body temperature. Hyperthermia can rapidly slow down baby’s progress and response to treatment. High sunlight intensity in tropical countries such as Nigeria manifests in incessant high neonatal temperatures towards early evenings. The ugly consequences of this neonatal evening-fever syndrome (EFS) can only be eradicated by the development of a controlled weatherproof nursery environment. Two laboratories and a ‘control ward’ were applied. Lab-2 was a renovation of an existing room in a manner that could correct an existing nursery. Lab-1 was an entirely new building idea. The laboratories were assessed based on comparative ability to maintain environmental coolness and neonatal thermal stability during hot days. Data collection continued for 12 full calendar months. On average, at evaluated out-wind peak temperature of 43°C (range: 41°C–46°C), the control-ward peak was at 39°C, Lab-2 peak at 36°C, and Lab-1 peak at 33°C. All incubators in the control overheated during the hot periods but there was no overheating in Lab-1. Forty-four (86%) of sampled babies were fever-quenched by water sponging 131 times in the control whilst only one baby received same treatment in Lab-1. Nursery designs patterned after Lab-1 can significantly reduce EFS-induced neonatal morbidity.